Identification and Assessment of Forest Fire in Similipal Tiger Reserve (STR) with GIS - Swain, Sanjay Kumar; Swain, Kishore Chandra (Indian Forester, 2019)
Forest fire is a major environmental issue, creating economical and ecological damage while endangering human lives. Similipal, situated at the Indian state of Odisha, is the only tiger reserve in the world, where the melanistic form of tiger is found and is properly conserved. The paper has tried to identify and evaluate the forest fire incidences in Similipal Tiger Reserve (STR) using Remote Sensing (RS) and GIS technique for four years, such as 2006, 2009, 2013 and 2016. Primary fire incidences data were collected from respective meteorological offices along with location co-ordinates with prevailing weather conditions. The forest fire incidences are mapped in Arc GIS 10.1 software environment. It shows unusual distribution of forest fire incidences in STR. The year 2009 has the maximum number of forest fire incidences in STR underlined by extremely hot weather and low precipitation condition. Ground truthing in the STR shows disturbances due to anti-social activities in some patches of the area, limiting the scope for preventive measures, caused large number of forest fires incidences. Forest fire caused by local people (man-made) associated with the presence of Particularly Vulnerable Tribal Groups (PVTGs) also are increased in numbers. Forest fire incidences can be reduced drastically with future planning and using modern technologies under most unfavourable climatic conditions.